2008
DOI: 10.1016/j.camwa.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of site effects on inelastic displacement ratios for SDOF and MDOF systems

Abstract: Lateral displacements' control of structures subjected to earthquake ground motion has now been recognized as a key factor in the assessment of system performance, leading to design approaches that use displacements rather than forces as the starting point for the seismic evaluation of structures. In fact performance-based approaches offer significant advantages in comparison with traditional force-based approaches, since the former are capable of focusing on nonlinear behaviour and consequent damage to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
1
13
0
4
Order By: Relevance
“…(11)- (14) and Table 5. Similar expressions can be provided for any possible combination of local site conditions, seismic sequence, critical damping and post-yield stiffness ratios.…”
Section: Inelastic Displacement Ratios For Multiple Earthquakes and Vmentioning
confidence: 96%
See 1 more Smart Citation
“…(11)- (14) and Table 5. Similar expressions can be provided for any possible combination of local site conditions, seismic sequence, critical damping and post-yield stiffness ratios.…”
Section: Inelastic Displacement Ratios For Multiple Earthquakes and Vmentioning
confidence: 96%
“…However, Miranda [7], Decanini et al [8], Ruiz-Garcia and Miranda [9,10] and Chopra and Chintanapakdee [11] showed that the inelastic displacement ratio can diverge significantly from unity in the moderately high to high frequency spectral regions. Recent investigations have shown that current standards used as the starting point for the seismic design of new structures, as well as of the seismic assessment of existing ones, can be significantly improved through an explicit account of lateral displacement demands [12][13][14][15]. The influence of various parameters on the inelastic displacement ratio is also examined in the abovementioned works.…”
Section: Introductionmentioning
confidence: 97%
“…Many research works have examined the evaluation of inelastic demands for structures under farfield ground motions [Miranda, 1993[Miranda, , 2000[Miranda, , 2001Chopra and Goel, 2000;Miranda and Jorge, 2002;Riddle et al, 2002;Decanini et al, 2003;Ruiz-Garcia andMiranda 2003, 2006;Mollaioli and Bruno, 2008]. It is well known that characteristics of ground motions close to the earthquake source can be considerably different from those of far-field motions in that they often contain a velocity pulse and permanent ground displacement [Somerville and Graves 1993].…”
Section: Introductionmentioning
confidence: 98%
“…see [1][2][3][4]). In the performance-based philosophy, in fact, the design criteria are expressed in terms of achieving different performance objectives for different levels of seismic hazard [5,6].…”
Section: Introductionmentioning
confidence: 94%